Subsurface Pore Water Contributions to Stream Concentration-Discharge Relations Across a Snowmelt Hydrograph - Olshansky, Yaniv; White, Alissa M.; Moravec, Bryan G.; McIntosh, Jennifer; Chorover, Jon (Frontiers in Earth Science, 2018)
This study investigated the concentration discharge (C-Q) patterns of selected elements transported to streams during spring snowmelt through an instrumented mixed-conifer forested catchment in rhyolitic terrain in the Jemez Mountains (NM, USA). High frequency, concurrent sampling of soil solution and gases, groundwater, and surface water enabled identification and sourcing of five groups of solutes with distinct C-Q behavior. Non-hydrolysing cations and strong acid anions, had mostly positive C-Q relations and a clockwise hysteresis pattern related to flushing of a limited reservoir of solutes accumulated in soils under snowpack. Rare earth elements (REEs) and dissolved organic carbon (DOC), demonstrated large positive C-Q relations and a clockwise hysteresis pattern, consistent with their co-transport as metal-ligand complexes, and signaling bio-weathering reactions in the soil. Silicon and dissolved inorganic carbon (DIC) exhibited chemostatic C-Q trends and an anti-clockwise hysteresis pattern consistent with sourcing from deep groundwater. Hydrolyzing metals (Mn, Al, Ti and Zr) with high coefficients of variance (CV) for concentration relative to CV values for stream discharge and with no significant C-Q pattern, were found to be transported mainly as filterable colloids. Fe C-Q behavior was similar to this hydrolyzing metals group, but complexation with DOC was also important for Fe during the initial stage of the snowmelt hydrograph. Investigation of time-series of solutes and gases provided evidence for biologically-induced silicate weathering reactions that initiated in the soil subsurface and propagated down through groundwater to streams.